Fenomena Relawan Politik dan Potensi Praktik Klientelisme Pada Pemilu 2024 di Provinsi Lampung - Gede Ari Pratama Putra; Hertanto Hertanto; Arizka Warganegara (Universitas Medan Area, 2022)
The 2024 Simultaneous Elections have attracted public participation by forming political volunteers supporting presidential candidates even before the candidates who will run in the election are determined. This qualitative research use observation and literature studies to examine the political participation of people who form political volunteers and the variety of clientelism practices based on market approaches according to Aspinal and Berenshot (2019). This study discovered that political volunteers grew and developed because of presidential candidates' need for political marketing services in the 2024 presidential election, which were offered to maximize the potential of Lampung Province's people, which has the eighth-largest population in the country and diverse demographic conditions. In conclusion, political volunteers act as brokers in clientelistic relations with candidates to increase popularity and build a base of supporters based on the segmentation of certain communities.